DOI: 10.31274/rtd-180813-13265
|View full text |Cite
|
Sign up to set email alerts
|

The use of real-time ultrasound and live animal measurements to predict carcass composition in beef cattle

Abstract: This manuscript has been reproduced from the microfilm master. UMl films the text directly fi'om the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter fece, while others may be from any type of computer printer. The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…As a noninvasive substitute for the ruler probe ultrasonic equipment was used to measure fat thickness which is easy to obtain on the live animal. These measurement improve prediction capacity of ultrasounds of 12-13th rib fat and longissimus muscle area [13]. Ultrasound technicians measures on the frozen image digitally on a computer.…”
Section: Live Animal Carcass Evaluationmentioning
confidence: 86%
See 2 more Smart Citations
“…As a noninvasive substitute for the ruler probe ultrasonic equipment was used to measure fat thickness which is easy to obtain on the live animal. These measurement improve prediction capacity of ultrasounds of 12-13th rib fat and longissimus muscle area [13]. Ultrasound technicians measures on the frozen image digitally on a computer.…”
Section: Live Animal Carcass Evaluationmentioning
confidence: 86%
“…The real time ultrasound using sound display muscle and fat tissues under a live animal hide [7]. Live animal body composition can be determined some time before sending to slaughter houses, this is a very important tool for price determination early stage without slaughter [8]. Carcass evaluation is a very important stage for better beef production.…”
Section: Live Animal Carcass Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The average correlations for rump fat and rib fat with carcass measurements were .92 and .90 with an average residual SEP of 1 mm. Duello et al (1992) reported a correlation in rib fat of .86 in relation to carcass measurement and Greiner (1997) reported .89 for rib fat. In the past, correlations of rib fat between ultrasound and carcass measurements ranged from .75 to .96 with an average of .86 (Houghton and Turlington, 1992).…”
Section: Fat Thicknessmentioning
confidence: 98%
“…In a study done by Greiner (1997), research was conducted on 534 steers to relate ultrasound as a predictor of retail product. The R2 value for weight of retail product in ultrasound using final weight, rib fat, ribeye area, and rump fat was .84.…”
Section: Carcass Traits Vs Ultrasound Traitsmentioning
confidence: 99%